Intercropping of corn and legumes with application of chicken manure and crop combination ratios to increase yield and quality of corn-legume forage - Baghdadi, Ali (2015)
Corn silage is an important feed for intensive ruminant production but the growing of corn has relied heavily on the use of chemical fertilizer. Experiments were conducted to determine the appropriate technology of corn-legume intercropping with supplemental use of chemical, organic manure and biofertilizer. In experiment one, three species of legumes: stylo (Stylosanthes guianensis), soybean (Glycine max) and mungbean (Vigna radiata) were intercropped with corn to select the best legume species to use for intercropping. Results indicated that corn-soybean intercropping gave the highest mixed forage dry matter (14.10 t/ha) compared to corn-mungbean (13.22 t/ha) and corn-stylo intercropping (8.77 t/ha) (p<0.05). Corn-soybean intercropping produced good quality feed in terms of the nutritive quality of forage and volatile fatty acids (VFA) of silage. Soybean contributed to increased crude protein (CP) in mixed corn-soybean forage (14.11%) in comparison with sole corn crop (10.05%), corn-mungbean (13.14%) and corn-stylo (11.28%) (p<0.05). Corn-soybean intercropping gave the highest forage protein yield (1990 kg/ha) (p<0.05) in comparison with corn monocrop (1415 kg/ha) and other corn-legume intercropped treatments. Higher level of CP, CP yield, leaves chlorophyll, leaf area index (LAI) and plant maturity of soybean than other legumes hence higher forage quality and DM of corn-soybean. In the second experiment, cornsoybean combinations of 75:25, 50:50 and 25:75 in addition to monocrops of corn and soybean were evaluated. The ratio of 75:25 and 50:50 recorded DM yields similar to those of monocropped corn (14.77 t/ha). Relative yield total (RYT) values of intercropping were higher than that of monocrop corn and soybean. Mixtures with 50:50 combination ratio had higher mean RYT values (1.15) (p<0.05) than the other ratios. Land equivalent ratio (LER) increased with corn-soybean intercropping and the highest total LER value was recorded with 50:50 ratio (1.13). Forage quality in terms of CP (75:25 ratio 12.75%, 50:50 ratio 13.73% and 25:75 ratio 14.68%) was improved by intercropping due to higher nitrogen availability for corn in intercropping compared with its sole crop (10.83% CP). Combination ratio of 50:50 gave higher protein yield (1886.45 kg/ha) than other crop combination ratio. The third experiment was carried out to evaluate effects of 10 types of fertilizer on corn-soybean forage yield and quality. Chemical fertilizer (NPK) gave significantly higher yield and quality of forage compared to organic and biofertilizer (p<0.05). Combining chemical fertilizers with chicken manure in a 50:50 ratio resulted in similar dry matter yield with the 100% NPK treatment. This might be attributed to the gradual release of essential nutrient from chemical and chicken manure (CM) fertilizer as required by the plants at all growth time. Combinations of NPK and CM resulted in increased plant height; crop growth rate (CGR) and LAI compared to CM alone but was similar to 100% NPK application. Similarly, CP content was not significantly different among 100% NPK (14.48%) and 50% CM+50% NPK (14.55%). Treatments with application of biofertilizer and combination of biofertilizer with NPK or CM treatments gave higher values of ARA compared to sole chemical and sole organic manure fertilizers. Overall, evidences recorded from this study prove that corn-soybean intercrops could increase forage quantity and quality, produce higher total protein yield, decrease requirements for protein supplements and chemical fertilizer compared to the corn monoculture with a 50:50 corn-soybean combination ratio and combination of chicken manure and chemical fertilizer.